International perspective on new pharmacy services - Tadić, Ivana (Archives of Pharmacy, 2022)
The global face of community pharmacy is changing. The trend in decreasing number of healthcare professionals, and partial overlapping of their roles, lead to development of new community pharmacy services that integrate multidisciplinary collaboration. The community pharmacy services development is recognised in several of the International Pharmaceutical Federation (FIP) development goals including goals for pharmacists’ education. According to the newest FIP report, community pharmacy services globally, apart from dispensing and supply of medicines, are categorised as: 1) services involving clinical decision-making for treatment initiation, continuation, or modification; 2) providing medicines and pharmaceutical care beyond the pharmacy premises; 3) disease screening; and 4) providing first aid/immediate care. Implementation of community pharmacy services should be based on scientific principles to achieve their effectiveness and sustainability. Implementation science aims to provide methods and strategies for effective service implementation. Based on many implementation researches several theories/frameworks were created to facilitate analysis of elements of each implementation step: factors/determinants which influence implementation, strategies and tools for evaluation. Further improvement and development of new community pharmacy services should be guided by global trends in development of community pharmacy services and strategies for their implementation.